Collaborative Cross mice reveal extreme epilepsy phenotypes and genetic loci for seizure susceptibility. (27th August 2020) - Gu, Bin; Shorter, John R.; Williams, Lucy H.; Bell, Timothy A.; Hock, Pablo; Dalton, Katherine A.; Pan, Yiyun; Miller, Darla R.; Shaw, Ginger D.; Philpot, Benjamin D.; Pardo‐Manuel de Villena, Fernando
Abstract: Objective: Animal studies remain essential for understanding mechanisms of epilepsy and identifying new therapeutic targets. However, existing animal models of epilepsy do not reflect the high level of genetic diversity found in the human population. The Collaborative Cross (CC) population is a genetically diverse recombinant inbred panel of mice. The CC offers large genotypic and phenotypic diversity, inbred strains with stable genomes that allow for repeated phenotypic measurements, and genomic tools including whole genome sequence to identify candidate genes and candidate variants. Methods: We evaluated multiple complex epileptic traits in a sampling of 35 CC inbred strains using the flurothyl‐induced seizure and kindling paradigm. We created an F2 population of 297 mice with extreme seizure susceptibility and performed quantitative trait loci (QTL) mapping to identify genomic regions associated with seizure sensitivity. We used quantitative RNA sequencing from CC hippocampal tissue to identify candidate genes and whole genome sequence to identify genetic variants likely affecting gene expression. Results: We identified new mouse models with extreme seizure susceptibility, seizure propagation, epileptogenesis, and SUDEP (sudden unexpected death in epilepsy). We performed QTL mapping and identified one known and seven novel loci associated with seizure sensitivity. We combined whole genome sequencing and hippocampal gene expression to pinpoint biologically plausible candidate genes (eg, Gabra2 ) and variants associated with seizure sensitivity. Significance: New mouse models of epilepsy are needed to better understand the complex genetic architecture of seizures and to identify therapeutics. We performed a phenotypic screen utilizing a novel genetic reference population of CC mice. The data we provide enable the identification of protective/risk genes and novel molecular mechanisms linked to complex seizure traits that are currently challenging to study and treat.